Simulation study of Fermi level depinning in metal-MoS2 contacts. (October 2021) - Khakbaz, P.; Driussi, F.; Giannozzi, P.; Gambi, A.; Esseni, D.
Highlights: Interface states in metal-MoS2 are presumably reason for the Fermi Level pinning. The Fermi level de-pinning could be attained by controlling the distance. With buffer layers and the use of back gate, the Schottky height can be zeroed. Abstract: We used Density Functional Theory (DFT) to study the Fermi level pinning and Schottky barrier height in metal-MoS2 contacts. We showed that the Fermi level de-pinning could be attained by controlling the distance between the metal and MoS2 . In particular, with proper buffer layers and the use of back-gated structures, the Schottky barrier height can be practically zeroed in some metal-MoS2 stacks, which is important to attain Ohmic contacts.